2010
DOI: 10.1177/0163278710370459
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Application to Eliminate Five Contraindicated Multiple-Choice Question Practices

Abstract: Multiple-choice questions (MCQs) evaluate factual knowledge in medical education and have a high reliability, if performed appropriately. However, many MCQs contain formal errors leading to reduced validity. The authors developed a Web application capable of recognizing and eliminating five frequent contraindicated practices in MCQs: negative stem, unfocused stem, cueing words, longest item ¼ right item flaw, and stem/item similarities. The authors used simple string algorithms and dynamic comparisons with key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Many other common flaws could be detected through algorithmic means (Vasiliki et al, 2015). Within this study, we simply counted the number of characters within each option in order to identify the longest one, but others have used computational techniques to look for the most linguistically complex option instead (Brunnquell et al, 2011). Post-test statistical analysis of MCQs by established methods such as Classical Test Theory, would provide additional information regarding which items are poorly discriminating, and so potentially assist human evaluators in identifying item flaws.…”
Section: Discussionmentioning
confidence: 99%
“…Many other common flaws could be detected through algorithmic means (Vasiliki et al, 2015). Within this study, we simply counted the number of characters within each option in order to identify the longest one, but others have used computational techniques to look for the most linguistically complex option instead (Brunnquell et al, 2011). Post-test statistical analysis of MCQs by established methods such as Classical Test Theory, would provide additional information regarding which items are poorly discriminating, and so potentially assist human evaluators in identifying item flaws.…”
Section: Discussionmentioning
confidence: 99%
“…The list of question flaws was generated by a literature review (11)(12)(13)16), referencing a local institutional guideline for MCQ writing (18), review of the American Board of Radiology item writers' guide (19), and the National Board of Medical Examiners' item writing guide (20). All commonly cited independent ''flaws,'' which violate standard evidencebased principles of effective item writing, were included in the analysis.…”
Section: Mcq Flawsmentioning
confidence: 99%
“…Questions that violate widely agreed on rules are described in the education literature as flawed (9)(10)(11)(12)(13). In simple terms, a flawed question tends to test ''how good of a test taker'' someone is, rather than the relevant knowledge intended, which can disadvantage some students (10).…”
mentioning
confidence: 99%
“…As a result demand for well-constructed MCQs has burgeoned. Studies have revealed, however, that examinations from medical school through CME are rife with questions that violate accepted standard question-writing principles [1][2][3][4][5][6]. In the medical education literature, the term for these nonstandard questions is "flawed" [1][2][3][7][8][9].…”
mentioning
confidence: 99%